A global dataset of demosponge distribution records - Ariadni Vafeiadou; Eliza Fragkopoulou; Jorge Assis (Data in Brief, 2024)
Biodiversity information in the form of species occurrence records is key for monitoring and predicting current and future biodiversity patterns, as well as for guiding conservation and management strategies. However, the reliability and accuracy of this information are frequently undermined by taxonomic and spatial errors. Additionally, biodiversity information facilities often share data in diverse incompatible formats, precluding seamless integration and interoperability. We provide a comprehensive quality-controlled dataset of occurrence records of the Class Demospongiae, which comprises 81% of the entire Porifera phylum. Demosponges are ecologically significant as they structure rich habitats and play a key role in nutrient cycling within marine benthic communities. The dataset aggregates occurrence records from multiple sources, employs dereplication and taxonomic curation techniques, and is flagged for potentially incorrect records based on expert knowledge regarding each species’ bathymetric and geographic distributions. It yields 417,626 records of 1,816 accepted demosponge species (of which 321,660 records of 1,495 species are flagged as potentially correct), which are provided under the FAIR principle of Findability, Accessibility, Interoperability and Reusability in the Darwin Core Standard. This dataset constitutes the most up-to-date baseline for studying demosponge diversity at the global scale, enabling researchers to examine biodiversity patterns (e.g., species richness and endemicity), and forecast potential distributional shifts under future scenarios of climate change.